2007
DOI: 10.1242/jcs.012138
|View full text |Cite
|
Sign up to set email alerts
|

Distinct endocytic pathways identified in tobacco pollen tubes using charged nanogold

Abstract: In an attempt to dissect endocytosis in Nicotiana tabacum L. pollen tubes, two different probes – positively or negatively charged nanogold – were employed. The destiny of internalized plasma membrane domains, carrying negatively or positively charged residues, was followed at the ultrastructural level and revealed distinct endocytic pathways. Time-course experiments and electron microscopy showed internalization of subapical plasma-membrane domains that were mainly recycled to the secretory pathway through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
199
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(209 citation statements)
references
References 45 publications
10
199
0
Order By: Relevance
“…For 120K to arrive at a vacuole, it must travel from the ECM through the pollen tube endomembrane system. Recent work has highlighted two distinct endocytic pathways in pollen tubes (54,55). Both clathrin-coated and noncoated vesicle endocytic pathways exist; clathrincoated vesicles traffic to the trans-Golgi, whereas noncoated vesicles travel to the multivescular body and a vacuole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For 120K to arrive at a vacuole, it must travel from the ECM through the pollen tube endomembrane system. Recent work has highlighted two distinct endocytic pathways in pollen tubes (54,55). Both clathrin-coated and noncoated vesicle endocytic pathways exist; clathrincoated vesicles traffic to the trans-Golgi, whereas noncoated vesicles travel to the multivescular body and a vacuole.…”
Section: Discussionmentioning
confidence: 99%
“…Both clathrin-coated and noncoated vesicle endocytic pathways exist; clathrincoated vesicles traffic to the trans-Golgi, whereas noncoated vesicles travel to the multivescular body and a vacuole. However, there is evidence that these two pathways are not mutually exclusive, suggesting that there is some degree of sorting of endocytic vesicles and their cargo (54). If endocytic vesicles contain many molecules with different destinations, these molecules need to be sorted consistently if they are to reliably arrive to their final destination.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the well-studied clathrin-dependent endocytosis (Chen et al, 2011), other entry pathways, including membrane raftmediated endocytosis, also operate in plant cells (Murphy et al, 2005;Moscatelli et al, 2007;Bandmann and Homann, 2011). Recent studies suggested that plant flotillins play a critical role in symbiotic bacterial infection of M. truncatula (Haney and Long, 2010;Haney et al, 2011), and the recycling of PIN proteins may depend on structural sterols and membrane rafts in Arabidopsis Willemsen et al, 2003;Men et al, 2008).…”
Section: Flot1 Participates In Non-clathrin-mediated Endocytosismentioning
confidence: 99%
“…These vesicles move along actin microfilaments to the apical domain where they undergo exocytosis, fusing with the apical plasma membrane and contributing their contents to the cell wall (Heslop-Harrison, 1987;Steer and Steer, 1989;Lancelle and Hepler, 1992;Cheung and Wu, 2008). Due to the necessity of maintaining the appropriate surface-to-volume ratio, much of the secreted membrane is reclaimed by endocytosis (Picton and Steer, 1983;Moscatelli et al, 2007;Bove et al, 2008;Ketelaar et al, 2008). Endocytotic vesicles may quickly cycle back and revisit the apical plasma membrane, or they may join the reverse fountain streaming pattern and be transported toward the base of the pollen tube (Parton et al, 2001;Bove et al, 2008).…”
Section: Introductionmentioning
confidence: 99%